THE RELATIONSHIP OF PHYSICAL DISTANCING WITH MENTAL HEALTH OF INDONESIAN COMMUNITY DURING COVID-19 - Enny Virda Yuniarti; Arief Andriyanto (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Background: The spread of the COVID-19 virus has spread widely throughout the world, which affects various aspects (Lebov et al., 2017). Several aspects affected by the transmission of the COVID-19 virus are psychological / mental health impacts caused by the implementation of policies from various countries in the form of a physical distancing system (Ornell, Schuch, Sordi, & Kessler, 2020). Objectives: Analyze the relationship between physical distancing and the mental health of Indonesian community during Covid-19. Methods: The cross-sectional study design. The sample of the study was the Indonesian people affected by the covid-19 pandemic who were taken based on purposive sampling with complete answer criteria as many as 1,090 respondents. The research instrument consisted of 2 questionnaires, including: a method questionnaire in physical distancing practices methods consisting of 11 items of physical distancing application to prevent the spread of the Covid-19 virus as recommended by World Health Organization. The Self-Reporting Questionnaire-29 is a questionnaire issued by the Directorate of Mental Health Services of the Indonesian Ministry of Health with the domains of anxiety and depression, psychomatics, symptoms of psychotic disorders, trauma stress. Parametric statistical tests used the Pearson test (p-value < 0.05). Results: The results obtained a p-value of 0.03, which means that there is a physical distancing relationship with the mental health of the Indonesian people during Covid-19. Conclusion: There is a significant relationship between physical distancing and the mental health of the Indonesian people. Recommendations for health workers, especially nurses in providing health services to the community, must be more comprehensive and recognize client responses to prevent psychological impacts.